2013
DOI: 10.1111/jfr3.12027
|View full text |Cite
|
Sign up to set email alerts
|

Broad scale quantified flood risk analysis in the Taihu Basin, China

Abstract: A geographic information system (GIS)-based analysis tool, the Taihu Basin Risk Assessment System (TBRAS), is developed to perform scenario analysis of future flood risk changes in the Taihu Basin. The TBRAS integrates modules of climate modelling, hydrological and hydraulic modelling, dyke reliability analysis, socioeconomic analysis, and damage assessment. The results indicate that the TBRAS can provide a broad-scale simulation of the flooding processes and damage evaluation for the entire Taihu Basin. Futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Climate input analysis [27] Economic assessments [29] Flood damage assessments [30] Hydrological data collection and frequency analysis…”
Section: R-d Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate input analysis [27] Economic assessments [29] Flood damage assessments [30] Hydrological data collection and frequency analysis…”
Section: R-d Modellingmentioning
confidence: 99%
“…Flood Damage Assessments. The Taihu Basin Risk Assessment System (TBRAS) risk analysis model is established to model inundation depths in the flood cells and calculate associated economic damage[30].…”
mentioning
confidence: 99%
“…In the past 30 years, large-scale flood events (in 1991, 1999 and 2016) have occurred in the TLB. Local flood events are more frequent, and some studies have indicated that the frequency and risk of future floods in the TLB will increase further [31,32]. Therefore, clarifying the impact of LULC change on hydrological processes in the TLB will help with water resource management in the basin, thereby reducing the risk of flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to solve Equation (3), it is necessary to determine the probability distribution of the flood events, their depths, and the associated damage. In general, a damage probability curve is built based on different flood return periods (Yu, Hall, Cheng, & Evans, 2013).…”
Section: Methodsmentioning
confidence: 99%